Metabolomic Profiling Reveals Potential Biomarkers and Prominent Features in HIV/AIDS Patients Co-Infected with SARS-CoV-2 - Xuan Yan; Xinyu Zhang; Wei Song; Tangkai Qi; Zhenyan Wang; Yang Tang; Jianjun Sun; Shuibao Xu; Junyang Yang; Jiangrong Wang; Jun Chen; Renfang Zhang; et al. (Microorganisms)
The underlying mechanisms and diagnostic biomarkers for the progress of COVID-19 in HIV patients have not been fully elucidated. In this study, the aim is to analyze the metabolomic profiles of HIV/AIDS patients co-infected with SARS-CoV-2 and to identify biomarkers indicative of co-infection. In this study, we conducted a retrospective cohort analysis of peripheral blood samples collected from 30 HIV/AIDS patients co-infected with SARS-CoV-2 (pc group) and 30 patients without SARS-CoV-2 (nc group). In this study, through non-targeted metabolomics and lipidomics analysis, 77 differential metabolites were identified in the plasma of patients co-infected with HIV and SARS-CoV-2 compared to the nc group, with vitamin K1 emerging as a significant feature. Moreover, the plasma of the pc group showed disturbances in lipid metabolism, with elevated triglycerides (TG) and phosphatidylcholine (PC) and decreased phosphatidylglycerol (PG) compared to the control group. Vitamin K1 may be a biomarker for SARS-CoV-2 in HIV/AIDS patients, and changes in the levels of TG, PC, and PG molecules appear to be the main features following HIV co-infection with COVID-19. The emphasis in our study is on the power of using comprehensive metabolomics (lipidomics) approaches to identify metabolic biomarkers and potential mechanisms of COVID-19 in HIV/AIDS patients.